Stability of freeze-dried pH-responsive dextrin nanogels containing doxorubicin - Manchun, S.; Dass, Crispin; Sriamornsak, P. (2016)
© 2016 The Authors. Induction of non-specific toxicities by doxorubicin (DOX) has restricted conventional DOX-based chemotherapy. pH-responsive dextrin nanogels (DNGs) have been fabricated in order to incorporate and deliver DOX to specific (targeted) sites. However, adequate stability studies of DOX-loaded DNGs are required for selection of storage conditions. The aim of this study was therefore to evaluate the accelerated (25?°C/60% RH) and long-term (5?°C) stability of DNGs prepared with formaldehyde (FDNGs) and glyoxal (GDNGs) as cross-linker by determining the change in their physicochemical properties. The mean diameter decreased with time during long-term storage. The drug content between freshly prepared (initial day) and after storage at 5?°C for 180 days of DOX-loaded FDNGs and DOX-loaded GDNGs was not significantly different (p?>?0.05), but decreased after storage under the accelerated condition. The release of DOX from all DNGs was pH-dependent. However, DNGs kept under the accelerated condition showed higher amount of DOX release than those stored at 5?°C and the freshly prepared ones. The results indicate that the stability of DNGs could be improved by their storage at 5?°C.